Comparison of hot water immersion at self-adjusted maximum tolerable temperature, with or without the addition of salt, for rapid weight loss in mixed martial arts athletes. - Connor, John; Egan, Brendan (Biology of Sport, 2021)
Hot water immersion is used by athletes in weight category sports to produce rapid weight loss (RWL) by means of passive fluid loss, and often is performed with the addition of Epsom salts (magnesium sulphate). This study investigated the magnitude of body mass losses during hot water immersion with or without the addition of salt, with the temperature commencing at 37.8°C and being self-adjusted by participants to their maximum tolerable temperature. In a crossover design, eight male MMA athletes (29.4 ± 5.3 y; 1.83 ± 0.05 m; 85.0 ± 4.9 kg) performed a 20 min whole-body immersion followed by a 40 min wrap in a warm room, twice in sequence per visit. During one visit, only fresh water was used (FWB), and in the other visit, magnesium sulphate (1.6% wt/vol) was added to the bath (SWB). Prior to each visit, 24 h of carbohydrate, fibre and fluid restriction was undertaken. Water temperatures at the end of the first and second baths were ~39.0°C and ~39.5°C, respectively. Body mass losses induced by the hot bath protocols were 1.71 ± 0.70 kg and 1.66 ± 0.78 kg for FWB and SWB, respectively (P = 0.867 between trials, d = 0.07), and equivalent to ~2.0% body mass. Body mass lost during the entire RWL protocol was 4.5 ± 0.7%. Under the conditions employed, the magnitude of body mass lost in SWB was similar to FWB. Augmenting passive fluid loss during hot water immersion with the addition of salt may require a higher salt concentration than that presently utilised.